Multipurpose Community Centers in South Africa An Empirical Study of Select Municipalities - Mpehle, Zwelibanzi (Richtmann Publishing, 2012)
The provision of basic services to citizens in a fair and equitable manner has been achallenge for the South African government, given the history of segregation based on raceand color that was instituted by the apartheid regime. It is such a challenge that compelledthe present government to identify various alternative strategies that will enhance servicedelivery, hence the birth of an idea to establish Multipurpose Community Centers (MPCCs),which later became known as Thusong Service Centers (TSCs), to serve as the vehicle inenhancing service delivery. The aim of this study was to evaluate if the MPCCs (herein alsoreferred to as TSCs or Centers) established by the South African government do enhanceservice delivery to the previously marginalized communities. The study was conducted inthree provinces in South Africa, and in each province three municipalities where TSCs havebeen established were randomly chosen on the basis of their geographical location, namelyrural, semi-urban and urban areas where previously marginalized communities dwell.Stratified random sampling was utilized in gathering information as the researchertargeted four population groups, namely the beneficiaries of services, government officialswho service clients in the TSCs, center managers and provincial coordinators of the TSCs.The researcher utilized structured questionnaires to gather information from beneficiariesof services, semi-structured interview schedule for government officials, and an observationsheet to record how TSCs operate, and whether the government officials practice BathoPele Principles in serving recipients of services. This article argues that although theintroduction of such Centers was a noble idea and that the household access to basicservices has changed for the better in certain communities, the Centers have not beensuccessful in accelerating services in some communities as revealed by the study. One ofthe reasons these Centers are not successful is lack of consultation by government withcommunities and other relevant stakeholders in the establishment of some Centers toestablish what services need to be rendered. Furthermore, some Centers do not haveadequate physical and human resources, and the managers running these Centers are notadequately trained in managerial and other relevant skills. The study also revealed thatlack of funding makes it impossible for these Centers and services rendered sustainable,and lack of communication and coordination of activities between departments utilizingthe Centers render integrated service delivery. The article concludes by givingrecommendations that were carefully drawn from the analysis of the findings and theentire study.